Effect of reducing starter feed crude protein content with different volumes of milk on the performance of calves - Silva, Ana Caroline Ramos Teles da (2023)
The objective was to evaluate the influence of decreasing crude protein (CP) of the starter feed content according to increasing age on the development of dairy calves during the pre-weaning, weaning and post-weaning phases. Sixty crossbred heifers were randomly assigned at 4 days of age to one of six treatments: 4 L/d and starter feed with fixed CP (4L_FCP), 4 L/d and starter feed with decreasing CP (4L_DCP), 6 L/d and starter feed with fixed CP (6L_FCP), 6 L/d and starter feed with decreasing CP (6L_DCP), 8 L/d and starter feed with fixed CP (8L_FCP) and 8 L/d and starter feed with decreasing CP (8L_DCP). Animals submitted to the FCP treatment received 18% PB in the starter feed throughout the experiment, while those included in the DCP treatment received 25% PB in the starter feed from day 4 to day 24, 18% from day 25 to day 45 and 14% from day 46 to day 66. The animals had free access to water and starter feed and their consumption was measured daily, in addition, they were submitted to 3 digestibility tests, in which samples of feces, urine, blood and ruminal fluid were collected. At 67 days, gradual weaning began and at 73 days the animals were weaned and submitted to blood and ruminal fluid collection. At 74 days, the animals began to have access to corn silage and remained in the experiment until 80 days of age, when blood and ruminal fluid were collected again. In addition, body measurements and body weight were measured weekly since the beginning of the experiment and at 66 and 80 d the animals were submitted to ultrasonography of the mammary gland, to evaluate the influence of the treatments. In general, animals that received 8 and 6L/d had higher performance, digestibility, feed efficiency and N utilization than 4L/d, but at weaning, 4L/d animals had a higher ADG (607 g/d for 4 L, 545 g/d for 6 L and 293 g/day for 8 L). Body weight was higher in animals that consumed starter feed with CP fixed in the starter at 66 d (73.1 kg for FCP and 68.4 kg for DCP) and at weaning (77.4 kg for FCP and 71.2 kg for DCP). Post-weaning feed efficiency was higher in DCP animals (655 g/kg) compared to FCP animals (364 g/kg), in addition to the intake and excretion of N in feces, at 66 d it was higher for animals that consumed FCP (37.8 g/d for ingestion and 1.76 g/d for N in feces) when compared to those that consumed DCP (31.7 g/d for N intake and 1.31 g /d for N stools). The efficiency of N use and the serum concentration of IGF -I and glucose were lower for 4 L/d animals. For blood urea nitrogen (NUS), at 80 d we observed higher concentrations of NUS for all milk volumes; compared to starter feed at 24 (20.8 mg/dL), 66 (18 mg/dL), 73 (22.8 mg/dL) and 80 d (27.7 mg/dL) FCP animals had higher concentrations of NUS than DCP (17.6 mg /dL at 24 d, 12.5 mg/dL at 66 d, 11.8 mg/dL at 73 d, 21.1 mg/dL at 80 d). Acetic, propionic and butyric acids increased in relation to days, respectively. In addition, the concentrations of butyric and acetic acid in animals that received 4L/d were higher when associated with FCP (9.33 µmol/mL for butyric acid and 43.9 µmol/mL for acetic acid) than with DCP (5.73 µmol/mL for butyric acid and 30.8 µmol/mL/mL for acetic acid). In the mammary gland, the animals had better parenchyma deposition at 80 d (67.4 pixels/mm²) compared to 66 d (71.7 pixels/mm²). Regarding milk volume, 4 L/d (64.9 pixels/mm²) was better than 8 L/d (75.1 pixels/mm²) and 6 L/d (69.3 pixels/mm²) did not differ from 4 or 8 L. Animals of FCP treatments (67 .2 pixels/mm²) had better results compared to DCP animals (72.1 pixels/mm²). It can be concluded that animals that consume 6 L/d have shown a good performance, in addition to reducing costs and bringing less harm to the animals at the time of weaning. In relation to the starter diet, the animals submitted to the FCP strategy presented higher consumption and better performance in relation to the DCP animals. However, DCP animals had lower fecal N excretion at 66 d, and better EF post-weaning, proving to be an effective alternative to decrease N excretion, and that there is a potential for improvement in animal performance with the use of this strategy that should be better explored. Keywords: Nutrition. Development. Dairy calves.